Association of human leukocyte antigen with postherpetic neuralgia in Koreans. Issue 10 (25th July 2016) - Chung, Hye Yoon; Song, Eun Young; Yoon, Jung Ah; Suh, Dae Hun; Lee, Sang Chul; Kim, Yong Chul; Park, Myoung Hee
Abstract : Postherpetic neuralgia (PHN), the most frequent complication of varicella‐zoster virus reactivation, is characterized by pain that persists for more than 3 months, often for years after healing of zoster rash. A few studies revealing the association of human leukocyte antigen (HLA) with PHN have been reported, but only in the Japanese. The aim of this study was to investigate the primary HLA locus associated with PHN susceptibility in Koreans. We compared HLA‐A, ‐B, ‐C, and DRB1 genotypes of 66 PHN patients with those of 54 herpes zoster (HZ) patients without developing PHN and 235 healthy controls. Frequencies of HLA‐B*13, B*44, B*15 (B75), DRB1*10:01, and DRB1*12:02 were increased, and those of HLA‐C*01, C*12, and DRB1*01:01 were decreased in PHN patients compared to those in controls (each, p < 0.05). Among these alleles, only the frequency of HLA‐B*44 was significantly increased in PHN patients compared to that in HZ patients and the change was due to HLA‐B*44:03 (PHN vs controls, p = 0.043; PHN vs HZ, p = 0.012). The results suggest that HLA‐B*44:03 or other closely linked gene of the major histocompatibility complex is associated with susceptibility to the development of PHN after HZ, but not with the onset of HZ.